2015
DOI: 10.1097/prs.0000000000000793
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively Activated M2 Macrophages Improve Autologous Fat Graft Survival in a Mouse Model through Induction of Angiogenesis

Abstract: M2 macrophages improve autologous fat graft volume retention by stimulating angiogenesis. These findings provide proof-of-principle for development of fat grafting techniques that harness reparative properties of M2 macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 29 publications
1
63
1
2
Order By: Relevance
“…This theory is further supported by the work of Eto et al, 42 who have shown that proliferating adipose-derived stem cells repopulate nonviable portions of the fat graft and are responsible for much of the ultimate graft volume. In contrast to our earlier work 25 and that of Yoshimura et al, 43 who suggest that infiltrating cell replacement and vascular ingrowth are key to final graft volume, we observed improvement in graft volume and quality without an increase in vascularity, suggesting that N-acetylcysteine does not act by stimulating angiogenesis. This is in keeping with the work of Kølle et al, who observed no increase in vascular density 4 months after implantation of grafts enriched ex vivo with adipose-derived stem cells.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…This theory is further supported by the work of Eto et al, 42 who have shown that proliferating adipose-derived stem cells repopulate nonviable portions of the fat graft and are responsible for much of the ultimate graft volume. In contrast to our earlier work 25 and that of Yoshimura et al, 43 who suggest that infiltrating cell replacement and vascular ingrowth are key to final graft volume, we observed improvement in graft volume and quality without an increase in vascularity, suggesting that N-acetylcysteine does not act by stimulating angiogenesis. This is in keeping with the work of Kølle et al, who observed no increase in vascular density 4 months after implantation of grafts enriched ex vivo with adipose-derived stem cells.…”
Section: Discussioncontrasting
confidence: 84%
“…25,26 Baseline micro-computed tomographic scans were obtained at day 4 and then again at 1 and 3 months after injection using a Flex Triumph in vivo microcomputed tomographic scanner (Gamma Medica, Inc., Salem, N.H.). The imaging protocol was 8.53 minutes, with a voxel resolution of 102 μm with 512 views and x-ray voltage of 70 kVp with anode current of 160 mA.…”
Section: Volumetric Analysismentioning
confidence: 99%
“…[1][2][3][4][5]8,9,15,22 Autologous fat grafts were combined with numerous different agents in recent years to increase their viability and decrease the rate of resorption including stem cell therapies; growth factors such as platelet-derived growth factor (PDGF), basic fibroblast growth factor (bFGF), vascular endothelial growth factor (VEGF), and epidermal growth factor (EGF); and other agents such as platelet-rich plasma (PRP), activated M2 macrophages, polymer therapy, and matrix metalloproteinase-2. [23][24][25][26][27][28][29][30] All of these agents and modalities demonstrated variable effects on the survival of fat grafts; however, none of them can be considered as the preferred method or agent for this issue. DFO is an ironchelating agent with numerous functions which directed us to research its effects on fat tissue transfer.…”
Section: Figmentioning
confidence: 99%
“…To understand the effect of collagenase digestion and SVF supplementation on micro-grafts, we used x-ray microtomography (micro-CT) to serially and noninvasively track the volume retention of human adipose tissue in a modified, published xenograft model 141,142 . This afforded the ability to serially track the volume of the grafted fat without the need to sacrifice the animal at each time point, something that has not been performed extensively in the literature.…”
Section: Overview Of Thesismentioning
confidence: 99%
“…In that same vein, supplementing the grafts with anti-inflammatory cytokines to combat this inflammatory environment would be an interesting study to conduct in the future. Interestingly, Phipps et al supplemented fat grafts with M2 macrophages and reported an increase in fat graft retention in a murine allograft model 142 . A better understanding of the effect of collagenase digestion on the proteins and cytokines within the adipose tissue may inform scientists and clinicians of ways to combat the decreased volume retention.…”
Section: Mechanism Responsible For Collagenase-induced Decreased Viabmentioning
confidence: 99%